The political elite of the North Caucasus during the revolution and civil war: plans and implementation of political concepts - Vladimir B. Lobanov (Кавказология)
The article handles the problems associated with modern Russian historiography devoted to the Revolution and the Civil War on the territory of the Terek and Dagestan regions in 1917-1921. Some argue the post-Soviet period provided Russian historians with a unique opportunity to explore previously little-studied topics related to administrative-territorial and national-state changes in the Terek-Dagestan region, with the history of the Cossacks and their participation in the anti-Bolshevik movement on the Terek. Historians also pay close attention to the study of issues related to the activities of the mountain liberal social movement, the influence of Islamists on revolutionary events in the region. It is concluded that the Russian historiography of the revolutionary period in the North Caucasus is experiencing a flourishing period; this topic attracts the attention of not only North Caucasian historians but also researchers from St. Petersburg, Moscow, Yekaterinburg.